An investigation on leakage problem in IBS building / Muhammad Farhan Afiq Zailan Kamaruddin - Zailan Kamaruddin, Muhammad Farhan Afiq (Faculty of Architecture, Planning and Surveying, 2013)
The Industrialised Building Systems (IBS) can be defiled in which all components such as the wall, slabs, beam, column and staircase are mass-produced either in factory or on the factory site under strict quality control and minimal wet site activities (Warswaski, 1999). This research is on the investigation on leakage problems in IBS buildings for a low cost housing project. The objectives of the study is to identify the effects of leakage in the IBS buildings, to understand on how the leakage problem arise to the IBS building and to give recommendation on how to improve the leakage problem so that it will not happen for the next construction. In order to achieve the objectives, face to face interviews with IBS Centre and also a total of 126 questionnaires has been distributed to the residents at two separate locations where the investigation is carried out which are in Section 17, Shah Alam and Section 24, Shah Alam. From this study, there are a lot of leakage problems that occurred at the case study that are not taken care off. It can be said that the leakage problem can affected the performance of the building. It is hope that this study can help to improve on the leakage problem problem so that it will not happen in the future projects.